Comparison of radii sets, entropy, QM methods, and sampling on MM-PBSA, MM-GBSA, and QM/MM-GBSA ligand binding energies of F. tularensis enoyl-ACP reductase (FabI) - Su, Pin-Chih (Journal of computational chemistry, 2015)
© 2015 Wiley Periodicals, Inc.